PREDICTIVE ANALYTICS AND IMMERSIVE STORYTELLING: THE ROLE OF AI AND AR/VR IN TAILORING DIGITAL ADVERTISING FOR UZBEKISTAN’S NICHE TOURISM MARKETS - Sodikov Mirziyo Odiljon ogli (European Science Publishing, 2025)
This article delves into the profound implications of integrating predictive analytics and immersive storytelling technologies—specifically Artificial Intelligence (AI) and Augmented Reality/Virtual Reality (AR/VR)—to revolutionize digital advertising for Uzbekistan’s burgeoning niche tourism markets. It posits that through the sophisticated application of AI to analyze extensive datasets and forecast nuanced consumer behaviors, coupled with the creation of deeply engaging, personalized, and culturally resonant immersive experiences facilitated by AR/VR, digital advertising can achieve unprecedented levels of efficacy and impact. The paper meticulously outlines a comprehensive conceptual framework for the strategic implementation of these advanced technologies, providing detailed insights into their potential applications across diverse niche markets prevalent in Uzbekistan. Furthermore, it critically examines the inherent challenges and substantial opportunities associated with large-scale adoption. The overarching objective is to demonstrate how these cutting-edge technological convergences can not only attract but also convert potential tourists by offering highly relevant, deeply captivating, and uniquely interactive digital interactions, thereby significantly bolstering Uzbekistan’s distinctive position as a premier global tourism destination.
Keywords: Predictive Analytics; Immersive Storytelling; Artificial Intelligence (AI); Augmented Reality (AR); Virtual Reality (VR); Digital Advertising; Niche Tourism; Uzbekistan; Hyper-Personalization; Cultural Engagement.